Changing Social Focusing in Indigenous Social Movements - Flynn, j. David; Hay, James M. (Journal of Sociocybernetics, 2014)
Using complexity science, we develop a theory to explain why some social movements develop through stages of increasing intensity which we define as an increase in  social focusing. We name six such stages of focusing: disintegration, revitalization, religious, organisation, militaristic, and self-immolation. Our theory uses two variables from the social sciences: differentiation and centrality, where differentiation refers to the internal structure of a social system and centrality measures the variety of incoming information. The ratio of the two, differentiation/centrality (the d/c ratio) is a shorthand way of saying that centrality must be matched by a corresponding level of differentiation to maintain basic focusing. If centrality exceeds differentiation, then the result is a lack of focusing—disintegration. On the other hand, the more differentiation exceeds centrality, the more the system moves into the higher stages of social focusing, from revitalization to the final stage of self-immolation.   To test the theory we examine historically indigenous social movements, in particular, the Grassy Narrows movement in northern Ontario Canada. We also suggest how the theory might be applied to explain other examples of social movement, especially millenarian movements at the end of the 20th century. We also suggest sociocybernetic ways the rest of society and the social movement itself can change its own social focusing.